Optimizing the Effectiveness of Human Resource Management in Audit Firms - Hoang, Dung Nguyen (Digital Repository of Theses - SSBM Geneva, 2025)
This study aims to optimize human resource management (HRM) effectiveness in small and medium-sized audit firms (SMAFs) in Hanoi, Vietnam, in response to the critical issue of high turnover among auditors with approximately three years of experience. With attrition rates exceeding 70%, this phenomenon severely disrupts workforce stability, increases operational costs, and weakens service quality and client confidence. The research employs a mixed-methods approach to provide a comprehensive analysis. Quantitative data were collected through surveys distributed to mid-level auditors to evaluate factors affecting job satisfaction, motivation, and retention. Qualitative data were obtained from semi-structured interviews with HR managers and firm leaders to gain insights into current HRM practices, perceived challenges, and strategic priorities. The findings indicate that high job pressure, limited career advancement, insufficient compensation, and a lack of managerial support are the key factors driving turnover. Quantitative analysis confirmed the statistical significance of these variables in predicting turnover intent, while qualitative data revealed gaps in HR planning, employee engagement, and professional development systems. The study proposes strategic HRM solutions tailored to the resource constraints of SMAFs. These include improving reward systems, defining transparent career pathways, enhancing training and development opportunities, and introducing flexible work arrangements to promote work-life balance. Emphasis is also placed on fostering a supportive organizational culture that values employee contribution and well-being. By implementing these recommendations, SMAFs can reduce employee turnover, improve workforce engagement, and strengthen their competitiveness in a demanding labor market. The study contributes to both academic knowledge and managerial practice by offering practical, context-specific strategies that align with the developmental needs of mid-level auditors and the operational realities of SMAFs.